2014
DOI: 10.15288/jsad.2014.75.228
|View full text |Cite
|
Sign up to set email alerts
|

A Mediational Model of Racial Discrimination and Alcohol-Related Problems Among African American College Students

Abstract: ABSTRACT. Objective: Racial discrimination has been identifi ed as an important predictor of alcohol-related outcomes for African Americans. The goal of the current study was to extend previously found links between lifetime discrimination, alcohol use, and alcohol problems as well as to elucidate the affective mechanisms underlying these associations, as moderated by gender. Method: A multiple-groups structural equation model was computed using survey data collected from 619 students from a historically Black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 46 publications
4
50
0
Order By: Relevance
“…These findings are consistent with evidence that African American men are more responsive to discrimination in terms of substance use than are women (Boynton et al, 2014;Brodish et al, 2011;Brody et al, 2012) and that men, in general, are more likely to drink in response to stress (Armeli et al, 2000;Ayer et al, 2011;Nesic & Duka, 2006). support (Scott, 2004;Swim et al, 2003).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These findings are consistent with evidence that African American men are more responsive to discrimination in terms of substance use than are women (Boynton et al, 2014;Brodish et al, 2011;Brody et al, 2012) and that men, in general, are more likely to drink in response to stress (Armeli et al, 2000;Ayer et al, 2011;Nesic & Duka, 2006). support (Scott, 2004;Swim et al, 2003).…”
Section: Discussionsupporting
confidence: 85%
“…Yet discrimination itself produces negative moods (Ong et al, 2009), which could lead to drinking as a coping response . This pattern of mediation has been demonstrated in longitudinal studies (e.g., Boynton et al, 2014;Gibbons et al, 2010) but has yet to be shown with micro-longitudinal data. However, we did not measure the source of negative moods and thus could not determine whether specific stressors, especially those related to race, showed unique associations with evening levels of alcohol use.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Moreover, drinking-to-cope motivation appears to escalate throughout young adulthood among African Americans, and this group has exhibited stronger links from coping motives to alcohol use and drinking problems than European Americans (Cooper et al, 1995, 2008). It has been theorized that African Americans may be more likely to drink to cope due to their elevated exposure to chronic stressors, such as social disadvantage, racial stigma/discrimination, and unfair treatment, all of which predict problematic drinking (Boynton, O’Hara, Covault, Scott, & Tennen, in press; Gerrard et al, 2012; Mulia, Ye, Zemore, & Greenfield, 2008; Mulia & Zemore, 2012). Although the current study focused on a well-educated population of African Americans, these students likely still experience many stressors related to race and other social factors that could motivate alcohol use as a means of coping.…”
Section: Drinking To Cope Among African Americansmentioning
confidence: 99%